TRANSFORMATION OF GOVERNANCE IN STATE-OWNED COMPANIES: THE CASE OF SOUTH AFRICA AS A DEVELOPING COUNTRY - Malgas, Maphelo; Zondi, Bonginkosi Wellington (Archives of Business Research, 2021)
The basis of this article is an article published by Thomas (2012) whose objective was to track over a two-year period the performance of five strategic South African state-owned enterprises with regards to issues of governance. These enterprises were ESKOM, South African Airways (SAA), South African Broadcasting Corporation (SABC), Telkom, and Transnet. The paper revealed that there were serious transgressions in these entities and recommendations were made to address these. The aim of this article therefore was to establish whether or not the transgressions reported by Thomas are still happening within these entities. The data was collected from the 2014/2015, 2015/2016, 2016/2017, and 2017/2018 financial reports of these entities. The study revealed that the transgressions are still taking place. With regards to issues of sustainability SAA and SABC continue to make loses, with SAA continuing to be bailed out by the South African government against the will of the South African general public. Fruitless and wasteful expenditure increased in all the five entities mentioned above and no serious action has been taken by the South African government to hold the people responsible accountable. While Telkom, Transnet and Eskom were making profits these profits are not at the envisaged level.